Seasonal and Spatial Changes of Primary Production in the Baltic Sea (Europe) Based on in situ Measurements in the Period of 1993–2018 - Zdun, Agnieszka; Stoń-Egiert, Joanna; Ficek, Dariusz; Ostrowska, Mirosława (Frontiers in Marine Science, 2021)
The seasonal and spatial variability of primary production (PP) measured using 14C method in two regions: open waters of the Baltic Sea and the Gulf of Gdansk were discussed. The statistical analyses of 26-years dataset (from 1993 to 2018) allow to confirm some regularities of productivity and find some features resulting mainly from changing environmental conditions like solar insolation, temperature, and chlorophyll a concentration. In the dataset, production values varied from 0.005 to 7.8 g C m–2 day–1 in open waters and from 0.07 to 12.9 g C m–2 day–1 in the Gulf of Gdansk. Analysis showed that PP in open waters were 6–17% lower than in Gulf of Gdansk in most of the cases. In both regions, the periods of intense productivity in spring and autumn were observed, but vegetation begins a month earlier in the Gulf of Gdansk than in open waters. Probably the accumulation of nutrients after the winter causes the spring bloom (April–May) in both regions to be more intense (even two times higher) than the autumn bloom (September–October) associated with favorable hydrological conditions resulting from summer insolation. The presented results showed slight downward trends in productivity in both regions, the most visible in the spring in the Bay of Gdansk. This confirms the recent reports on a possible improvement in the eutrophication state of the Baltic Sea.